Social justice leadership: implications for roles and responsibilities of school administrators - Turhan, Muhammed (Elsevier Science Bv, 2010)
Social justice is an issue widely debated in the literature. In particular, the roles and responsibilities of school administrators and teachers to ensure social justice in education have been discussed intensively. These discussions have led to emerging of social justice leadership as a new type of leadership and working on. The main purpose of this article is to make an analysis of social justice and social justice leadership based on the literature and to review roles and responsibilities of school administrators related to social justice leadership. Firstly a broad definition of the concept of social justice has been done. Secondly the concept of social justice leadership has been examined and this new type of leadership and its relationships with other types of leadership have been analyzed. Finally the roles and responsibilities of school administrators related to social justice leadership for creation socially just schools have been discussed. (C) 2010 Published by Elsevier Ltd.
1st World Conference on Learning, Teaching and Administration (WCLTA) -- OCT 29-31, 2010 -- Amer Univ, Cairo, EGYPT
Keywords: Social justice; leadership; social justice leadership; roles of school administrators